1999
DOI: 10.1123/pes.11.4.317
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Determinants of Maximal Aerobic Power in Healthy 12-Year-Old Boys

Abstract: Little is known regarding the physiological determinants of maximal oxygen uptake (VO2max) in children. A group of 39 healthy sixth-grade boys (mean age, 12.2 years) underwent maximal cycle testing with determination of cardiovascular factors using Doppler echocardiography as well as standard gas exchange variables. Maximal stroke index was related to VO2max/kg (r=0.52, p < .05), but no relationship was observed between VO2max/kg and either maximal heart rate or calculated maximal arteriovenous oxygen diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Moreover, the pattern of diminished stroke index and cardiac index observed in this study is consistent with that observed in healthy youths with low fitness. 24 However, involvement in sports teams and physical activity level by questionnaire were similar among patients with pectus deformity and control boys in this study. Eighteen of the 21 patients with pectus excavatum studied by Malek et al 5 had been performing regular aerobic activity 30 minutes to 2 hours daily an average of 3 times a week.…”
Section: Depressed Aerobic Fitness From Sedentary Lifestylementioning
confidence: 45%
“…Moreover, the pattern of diminished stroke index and cardiac index observed in this study is consistent with that observed in healthy youths with low fitness. 24 However, involvement in sports teams and physical activity level by questionnaire were similar among patients with pectus deformity and control boys in this study. Eighteen of the 21 patients with pectus excavatum studied by Malek et al 5 had been performing regular aerobic activity 30 minutes to 2 hours daily an average of 3 times a week.…”
Section: Depressed Aerobic Fitness From Sedentary Lifestylementioning
confidence: 45%
“…The boys were part of a larger group described in reports of the relationship of cardiovascular function with aerobic fitness 25 and field performance. 26 Findings for the girls have previously been presented in a comparison of cardiovascular fitness in premenarcheal girls and adult women.…”
Section: Methodsmentioning
confidence: 99%
“…Within studies, a-vO 2 diff max has consistently been reported to be higher in young adult men than in boys (Nottin et al 2002;Rowland et al 1997a), but data from studies focused on children and early adolescents indicate that a-vO 2 diff max is not influenced by age (Gilliam et al 1977;Rowland 2005;Yamaji and Miyashita 1977), sex (Obert et al 2003;Rowland et al 2000a;Vinet et al 2003), or maturity status (McNarry et al 2011(McNarry et al , 2014Rowland 2017). Significant associations between a-vO 2 diff max and peak V O 2 have not been identified in children and adolescents (Rowland 2017;Rowland et al 1999b).…”
Section: Introductionmentioning
confidence: 99%